RELATIONS BETWEEN THE SIGNSOFPHYSICAL CAPACITY OF 4TH GRADE STUDENTSIN FOLK DANCE TRAINING - T. Simeonova; Y. Yankov; N. Nikolova (Trakia Journal of Sciences, 2024)
The teaching of folk dances and dances in the 4th grade is included in the compulsory area of educational content in the Bulgarian school. After conducting an innovative program in the teaching of folk dances, the physical capacity of students were determined by accomplishing seven tests. The study found that dancing exerts a positive effect on the development of children's physical qualities. The correlations between the indicators of physical capacity of students proved the effectiveness of the proposed program.